The relationship between social frailty and cognitive impairment among older adults: the role of various types of internet use - Choi, Kyungwon; Ko, Young (Frontiers in Public Health, 2024)
This study aimed to explore the role of internet use in the relationship between social frailty and cognitive function among Korean older adults. A nationally representative survey of communitydwelling older adults in Korea was used in the analysis (N=8,639). All types of internet use were significantly associated with cognitive impairment and played a significant role in the relationship between social frailty and cognitive impairment. The advantage of internet use for information searching (OR 0.40, 95% CI 0.35-0.46) was the greatest for cognitive function, followed by internet use for instrumental use (OR 0.59, 95% CI 0.53-0.66). Internet use for entertainment exhibited the greatest influence in the relationship between social frailty and cognitive impairment, with interpersonal communication ranking second in significance. Internet use regulates the relationship between social frailty and cognitive impairment in older adults. The influences of internet use vary depending on the type of online activity and the levels of social frailty. This highlights the importance of considering various forms of internet use when developing non-pharmacological interventions to mitigate the impact of social frailty on cognitive decline.